Transposing Intersections? The change in relational paradigms in the art world of contemporary photography - Costa, P.; Lopes, R., V. (ACEI 2023 Conference - 22nd International Conference on Cultural Economics: “Cultural Economics, Coming Together: Bridging Distances, Crossing Boundaries”, 2023)
This paper aims to discuss and question the possibilities of a paradigmatic change in the relational logics between the different actors of the "art world" of contemporary photography (artists, curators, institutions, mediators,...), departing from the research made by the authors in the context of the project PARALLEL – European Photo Based Platform. This was a project, designed and led by Procur.arte, and co-funded by the Creative Europe Programme of the European Union, that intended to establish a platform to develop and network the work of new creators (artists and curators) and institutions (galleries, museums, festivals, educational institutions) which structure this "art world". PARALLEL Platform brings together more than 20 European cultural hubs in the contemporary photography art world, including museums, galleries, cultural centres, festivals, art schools and publishers. With origin in 19 different countries, ensuring a wide geographical spread across Europe, these institutions participate in selecting and hosting emerging artists and curators, organizing exhibitions and promoting artistic networking among them, fueling a link which often is subject to a diversity of problems and challenges, due to the traditional structuring mechanisms of the art worlds, both at national and international levels. Since its presupposition is the development of new practices and logics of exchange, in the fields of creation, curatorship and exhibition, it is important to analyze the practical results of the platform in the light of its primary objectives and to understand the extent to which it establishes or not some possibilities of structural change in the relations between the various actors of the respective art world. The analysis is carried out based on the direct observation of researchers, as well as a set of meetings, focus groups and interviews to the artists, curators and institutions involved in the 1st, 2nd and 3rd cycle of activities of the PARALLEL platform. The paper begins with two introductory sections: firstly, the contextualisation of PARALLEL project and secondly a panoramic overview on the activities developed in the scope of the project in its 1st and 2nd cycles. The third section bring us a comprehensive analysis of the perceptions of the participants on the results obtained concerning each of the six general objectives assumed by the platform, until the beginning of the 3rd cycle. Finally, in the two remaining sections, some conclusive notes are systematized in relation to the two main purposes of this research: on the one hand in relation to the way the project challenges the organization of the art world of contemporary photography; and on the other hand, gathering some lessons on aspects to be improved in the implementation of the platform.